PENGARUH PERUBAHAN NILAI TUKAR RUPIAH TERHADAP RETURA' SAHAM MELALUI PERUBAHAN ARUS KAS DAN PERUBAHAN EARNING PER SHARE (EPS): BUKTI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEJ - LIA INDRIYATI KURNIAWAN (Fakultas Bisnis UKDW, 2006)
The srudy is ot empirical one wlnse pwposes or,e to prove if exclwnge rate'risk have a positive inJluence in stock return from earning per share alteration and cash flow alteration. Samples which are used in this stut are 192 data of manufacturing corporations that listed inBEI. The period of sudy is 199&2004. &atistic mdels which are used in this study are simple regression od multiple regression analysis. Tlwre,wefow models used in this study. TTtere ue, model I and model II are used to prove if information of eorning per share alteration and cash flow alteration ltove a positive intluence for cumulative abnormal return. Model III and Model IY are used to pnove if exchange rate risk have a positive infiuence for earning per share alteration and cash flow alteration.The results are information of earning per share alteraion and cash flow alteration have not a positive inJluence for cumulative abnormal return, exchange rate risk have not a positive influence in eorning per share, but exchange rate risk altergtion have a positive influence for cash flow alteration.Keywords: Real Exchange Rate, Earning Per Share, Cash Flow